Research on Authentication Technology of Agriculture Products Traceability System Based on RFID - B. Wang; J. Zhang; X.H. Sun; N. Wang; Y. Zhao; F.S. Wang (Chemical Engineering Transactions, 2015)
A secure mutual authentication protocol named DRHSAP (Dynamic Refresh ID and Hash-based the Security authentication protocol) is presented. It can guarantee that the agriculture products in the process of productivity and circulation are not counterfeit. Based on the deficiencies of the low cost RFID (Radio Frequency Identification) system, the DRHSAP protocol has kept the last and present identities of each label on server to effectively solve the synchronization issue between the server and the label, thus further enhances the overall safety of the system. After using BAN logic and several comparative analysis of the authentication protocol, it can prove that the DRHSAP can effectively ensure the security and privacy issues faced by RFID technology and achieve higher security in RFID system.